Designers on design. - Conran, Terence, ....-; Fraser, Max, ....- (London : Conran Octopus, 2004)
Cell phones, watches, coffee cups, grand pianos, light fixtures, even a dog house. Consumer products are brought to life through designers' imagination and ingenuity, and Terence Conran and Max Fraser present some of the biggest names in the business and the items they've created. Between the covers of Designers on Design are interviews with more than a hundred designers, who answer such questions as: What was your big break?; What or who has most influenced your work?; What elements of the design process do you find particularly frustrating?; and To what level will you compromise to satisfy your client? This beautifully illustrated book shows key pieces from each designer, along with a timeline that highlights major developments in the field from the early 1900s to the beginning of this century. Designers on Design provides a rare insight into the creative thought processes of today's leading designers in their own words.
Keywords: Ontwerpers